Peripherally InSerted CEntral catheter dressing and securement in patients with cancer: the PISCES trial. Protocol for a 2x2 factorial, superiority randomised controlled trial. Issue 6 (15th June 2017) - Rickard, Claire M; Marsh, Nicole M; Webster, Joan; Gavin, Nicole C; Chan, Raymond J; McCarthy, Alexandra L; Mollee, Peter; Ullman, Amanda J; Kleidon, Tricia; Chopra, Vineet; Zhang, Li; McGrail, Matthew R; et al.
Abstract : Introduction: Around 30% of peripherally inserted central catheters (PICCs) fail from vascular, infectious or mechanical complications. Patients with cancer are at highest risk, and this increases morbidity, mortality and costs. Effective PICC dressing and securement may prevent PICC failure; however, no large randomised controlled trial (RCT) has compared alternative approaches. We designed this RCT to assess the clinical and cost-effectiveness of dressing and securements to prevent PICC failure. Methods and analysis: Pragmatic, multicentre, 2×2 factorial, superiority RCT of (1) dressings (chlorhexidine gluconate disc (CHG) vs no disc) and (2) securements (integrated securement dressing (ISD) vs securement device (SED)). A qualitative evaluation using a knowledge translation framework is included. Recruitment of 1240 patients will occur over 3 years with allocation concealment until randomisation by a centralised service. For the dressing hypothesis, we hypothesise CHG discs will reduce catheter-associated bloodstream infection (CABSI) compared with no CHG disc. For the securement hypothesis, we hypothesise that ISD will reduce composite PICC failure (infection (CABSI/local infection), occlusion, dislodgement or thrombosis), compared with SED. Secondary outcomes: types of PICC failure; safety; costs; dressing/securement failure; dwell time; microbial colonisation; reversible PICC complications and consumer acceptability. Relative incidence rates of CABSI and PICC failure/100 devices and/1000 PICC days (with 95% CIs) will summarise treatment impact. Kaplan-Meier survival curves (and log rank Mantel-Haenszel test) will compare outcomes over time. Secondary end points will be compared between groups using parametric/non-parametric techniques; p values <0.05 will be considered to be statistically significant. Ethics and dissemination: Ethical approval from Queensland Health (HREC/15/QRCH/241) and Griffith University (Ref. No. 2016/063). Results will be published. Trial registration: Trial registration number is: ACTRN12616000315415.